Environmental variation associated with topography explains butterfly diversity along a tropical elevation gradient. (23rd November 2021) - Cómbita, José Luís; Giraldo, Carlos E.; Escobar, Federico
Abstract: Few studies have evaluated the role of topography on the diversity patterns of biological communities along elevation gradients. We evaluated the influence of microclimate and vegetation structure associated with topographic variation on the richness and composition of species of different families of butterflies on a mountain located in a dry enclave (Chicamocha River Canyon) in the northern Andes, Colombia. We captured butterflies over four months at 18 elevations (300 to 1500 m a.s.l.) in two topographic positions (riverbed and hillslope) using an entomological net and traps baited with fermented fruit. In general, butterfly richness increased with elevation in both topographic positions. However, the richness–elevation relationship changed with butterfly family. The riverbed and hillslope sites host different assemblages of butterflies, and this pattern that was consistent for most families. In the riverbed, two sets of species are recognized along the elevation gradient (one below 700 m a.s.l. and the other above 1000 m a.s.l.), mainly owing to species replacement. On the hillslopes, there was no clear pattern of grouping associated with elevation. Microclimate differences between the riverbed and hillslope sites along the elevation gradient were related to the vegetation structure and explained the variation in butterfly species composition. Our results highlight the role of topography not only by explaining the response of species richness and composition to environmental variation determined by elevation, but also as a factor that must be considered in the planning and management of biodiversity conservation in the mountains. Abstract in Spanish is available with online material. Abstract : The butterfly richness increases with elevation. However, the richness–elevation relationship changed with the butterfly family. The riverbed and hillslope sites host different assemblages of butterflies and this pattern that was consistent for most families. Resumen: Pocos estudios han evaluado el papel de la topografía en la diversidad de las comunidades biológicas en gradientes de elevación. En este estudio exploramos la influencia del microclima y la estructura de la vegetación asociada a la topografía en los patrones de riqueza y composición de especies de diferentes familias de mariposas (Lepidoptera: Papilionoidea) en una montaña ubicada en el cañón del río Chicamocha, un enclave seco al norte de los Andes, Colombia. Capturamos mariposas durante cuatro meses en 18 elevaciones (300 a 1500 m s.n.m.) en dos diferentes posiciones topográficas (fondo fluvial y ladera) utilizando redes entomológicas y trampas con fruta fermentada. En general, la riqueza de mariposas aumenta con la elevación en ambas posiciones topográficas. Sin embargo, la relación riqueza‐elevación cambió al considerar la familia. Los sitios en fondo fluvial y ladera albergaron diferentes ensamblajes de mariposas y este patrón fue consistente para la mayoría de las familias. En los fondos fluviales, se reconocen dos conjuntos de especies en el gradiente de elevación (por debajo de 700 m s.n.m. y el otro por encima de 1000 m s.n.m.), determinados principalmente por el reemplazo de especies. Mientras que en las laderas no hubo un patrón claro de agrupación asociado con la elevación. Las diferencias microambientales asociadas con la estructura de la vegetación entre fondo y ladera a lo largo del gradiente de elevación, explicaron la variación en la composición de especies de mariposas. Nuestros resultados resaltan el papel de la topografía no solo para comprender la respuesta de la riqueza y composición de especies a la variación ambiental determinada por elevación, sino también como un factor que debe ser considerado para la planificación y gestión de la conservación de la biodiversidad en las montañas.